2018
DOI: 10.1111/oik.05331
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐ecosystem effects of a large terrestrial herbivore on stream ecosystem functioning

Abstract: Large terrestrial consumers have direct and indirect effects on forest ecosystem function, but few studies have investigated the impacts of terrestrial consumers on freshwater ecosystems. In the Cape Breton Highlands of Nova Scotia, browsing by hyper‐abundant moose following a spruce budworm outbreak has transformed boreal forest into grasslands. We conducted a field study to investigate the potential for cross‐ecosystem effects of hyper‐abundant moose following budworm outbreak on small boreal stream ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, this top‐down approach to estimating fixation may fail to capture areas of high fixation rates due to the abundant presence of N‐fixing tree species. For example, Cleveland et al () predict low rates of fixation in the Pacific Northwest, but this region is dominated by high‐fixing species like red alder where N inputs from fixation are known to be high (MacSween et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this top‐down approach to estimating fixation may fail to capture areas of high fixation rates due to the abundant presence of N‐fixing tree species. For example, Cleveland et al () predict low rates of fixation in the Pacific Northwest, but this region is dominated by high‐fixing species like red alder where N inputs from fixation are known to be high (MacSween et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research demonstrated that invertebrate herbivores [e.g., mountain pine beetle (Dendroctonus ponderosae) [4]] and invasive earthworms [31] can shift large regions of boreal forest from being a C sink to a C source during outbreak years. We surmise that large herbivore impacts will be greatest when mediated by natural and human disturbances [15,32] and that such impacts can lead to failed natural forest regeneration and alternative ecosystem states (Figure 2 and Box 1; [13,17,19]). Large herbivores have the capacity to respond quickly (e.g., increase in twinning rates of female moose) to favorable forage conditions created by large canopy openings, which ultimately increases their abundance.…”
Section: Glossarymentioning
confidence: 99%
“…While the influences of abiotic vectors on ecosystem dynamics have been extensively studied (Gravel, Guichard, et al 2010; Gravel, Mouquet, et al 2010; Gounand, Mouquet, et al 2014; Loreau, Daufresne, et al 2013), less is known about how flows mediated by biotic vectors affect ecosystem processes and functions (Gounand, Harvey, et al 2018; but see Subalusky, Dutton, Njoroge, et al 2018; Schmitz, Wilmers, et al 2018). Evidence from both the fossil record and present-day events shows that biotic drivers of ecosystem flows affect ecosystem functions at extents ranging from local to continental (Bauer and Hoye 2014; Schmitz, Raymond, et al 2014; Doughty 2017; MacSween, Leroux, and Oakes 2019). However, organism-driven exchanges have diminished over time as humankind began modifying the biosphere (from the late Quaternary onwards; Doughty et al 2016).…”
Section: Introductionmentioning
confidence: 99%